Stent-Assisted Coiling in Endovascular Treatment of 500 Consecutive Cerebral Aneurysms with Long-Term Follow-Up - Geyik, S. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Stent-assisted coil embolization has become one of the most preferred techniques in the treatment of wide-neck intracranial aneurysms; however, long-term patency and safety of the self-expanding neurostents and their role in durability of the endovascular treatment has remained ambiguous. We sought to retrospectively examine the long-term results of self-expanding stent usage in conjunction with coil embolization in treatment of wide-neck cerebral aneurysms. MATERIALS AND METHODS: We coiled 500 wide-neck cerebral aneurysms with different types of self-expanding neurostent assistance in 468 patients. Patient and aneurysm characteristics, pharmacologic therapy protocol, complications, and initial occlusion grades were analyzed. Patients underwent angiographic follow-up at 6 months to 7 years after treatment. DSA or MRA images of all patients were analyzed to assess the occlusion rate of aneurysms and patency of the parent artery. RESULTS: Enterprise (n = 340), Solitaire (n = 98), Wingspan (n = 41), LEO (n = 16), and Neuroform (n = 5) stent systems were used in this series. Stent-related thromboembolic events occurred in 21 patients and intraoperative rupture occurred in 4 patients. Initially, complete occlusion was achieved in 42.2% of the aneurysms, and, according to the last follow-up data, the rate had progressed to 90.8%. Recanalization rate at 6 months was 8%, whereas the late recanalization rate was 2%. CONCLUSIONS: The use of stents in endovascular treatment provides high rates of complete occlusion and low rates of recurrence at a long-term follow-up study.